Fine-Grained Network Traffic Identification Based on Tilera Platform - Shun Wu; Dan Su; Jia Wu; Kun Li; Dawei Xu; Yun Liu; Zheng Wei (Dianxin kexue)
It is essential for network managers to decide how to use a reasonable allocation of bandwidth, providing differentiated services, as well as conducting security monitor and management so as to do fine-grained and precise IT operation. The fine-grained traffic identification method proposed was able to identify the user's behavior accurately according to the traffic that the application generates. In addition, compared with the traditional x86 platform, in order to achieve higher throughput and lower power consumption, the method was redesigned and implemented in the Tilera platform with parallelization. Finally, a variety of system performance test results were compared under the two platforms.